Role of isotopes in microturbulence from linear to saturated Ohmic confinement regimes - Lei Qi; Jae-Min Kwon; T. S. Hahm; M. Leconte; Sumin Yi; Y. W. Cho; Janghoon Seo (Physical Review Research, 2024)
The first-principle gyrokinetic numerical experiments investigating the isotopic dependence of energy confinement achieve a quantitative agreement with experimental empirical scalings, particularly in Ohmic and L-mode tokamak plasmas. Mitigation of turbulence radial electric field intensity |δE_{r}|^{2} and associated poloidal δE×B fluctuating velocity with the radial correlation length l_{cr}∝M_{i}^{0.11} strongly deviating from the gyro-Bohm scaling is identified as the principal mechanism behind the isotope effects. Three primary contributors are classified: the deviation from gyro-Bohm scaling, zonal flow, and trapped electron turbulence stabilization. Zonal flow enhances isotope effects primarily through reinforcing the inverse dependence of turbulence decorrelation rate on isotope mass with ω_{c}∝M_{i}^{−0.76}, which markedly differs from the characteristic linear frequency. The findings offer insights into isotope effects, providing critical implications for energy confinement optimization in tokamak plasmas.